BRAND IMAGE AS A MEDIATOR BETWEEN DIGITAL MARKETING AND PURCHASE DECISIONS - Farid Eka Saputra; Muhammad Sholahuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research looks into how influencers, content marketing, and promotions affect brand image and buying choices, with brand image serving as an important link in the area of halal personal care items sold on the Shopee online platform. The study uses numbers and data gathered through surveys from Shopee customers who have bought halal personal care products. The information was examined through SEM. The findings show that influencers do not significantly improve brand image or buying choices. On the other hand, content marketing and promotions positively impact brand image in a significant way. Additionally, both content marketing and promotions also greatly affect buying choices. Brand image itself positively influences buying choices, underscoring its crucial role in guiding consumer habits. When it comes to mediation roles, brand image does not connect influencers with buying choices. However, it does play a significant part in connecting content marketing with buying choices. On the other hand, brand image does not link promotions to buying choices. In summary, these results emphasize that content marketing is the most important element in enhancing brand image and influencing buying choices for halal personal care products, while influencer marketing has a limited effect in this area. These findings suggest practical steps for online sellers and marketers to focus on high-quality and relevant content strategies while also running effective promotional campaigns to improve consumer buying choices.